2015
DOI: 10.1007/978-3-319-13960-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Massively Parallel NUMA-Aware Hash Joins

Abstract: Abstract. Driven by the two main hardware trends increasing main memory and massively parallel multi-core processing in the past few years, there has been much research eort in parallelizing well-known join algorithms. However, the non-uniform memory access (NUMA) of these architectures to main memory has only gained limited attention in the design of these algorithms. We study recent proposals of main memory hash join implementations and identify their major performance problems on NUMA architectures. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…For instance, Kim et al [1] look at the effects of caches and TLBs (translation lookaside buffers) on main-memory parallel hash joins and show how careful partitioning according to the cache and TLB sizes leads to improved performance. Along the same lines, Lang et al [2] have shown how tuning to the non-uniform memory access (NUMA) characteristics also leads to improved performance of parallel hash joins. We will refer to the algorithms that take hardware characteristics into consideration as hardware-conscious.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, Kim et al [1] look at the effects of caches and TLBs (translation lookaside buffers) on main-memory parallel hash joins and show how careful partitioning according to the cache and TLB sizes leads to improved performance. Along the same lines, Lang et al [2] have shown how tuning to the non-uniform memory access (NUMA) characteristics also leads to improved performance of parallel hash joins. We will refer to the algorithms that take hardware characteristics into consideration as hardware-conscious.…”
Section: Introductionmentioning
confidence: 92%
“…E.g., Albutiu et al [6] show that prefetching can hide the latency of remote accesses, constructing a competitive sort-merge join. Hash-joins, however, are shown to be superior [8,20]. Yinan et al [25] optimize data shuffling on a fully-interconnected NUMA topology.…”
Section: Related Workmentioning
confidence: 99%
“…[4] proposes a partitioned join that minimizes random inter-socket reads, and [15] improves upon that with a NUMA-aware data shuffling stage. [13] presents a latch-free hash table design for scalable NUMAaware build phase. We think that simplifying hash joins to a series of DIRA lookups will make hardware acceleration easier, because we can repeatedly use a gather primitive.…”
Section: Related Workmentioning
confidence: 99%